Radix Glycyrrhizae Preparata Induces Cell Cycle Arrest and Induced Caspase-Dependent Apoptosis in Glioblastoma Multiforme - Tsung-Ying Lin; Tung-Hsuan Wu; Rong-Dar Tzou; Yi-Chiang Hsu; Kuan-Ting Lee; Tai-Hsin Tsai (MDPI AG, 2022)
Glioblastoma multiforme (GBM) is a highly aggressive and devastating brain tumor characterized by poor prognosis and high rates of recurrence. Despite advances in multidisciplinary treatment, GBM constinues to have a poor overall survival. The Radix Glycyrrhizae Preparata (RGP) has been reported to possess anti-allergic, neuroprotective, antioxidative, and anti-inflammatory activities. However, it not clear what effect it may have on tumorigenesis in GBM. This study demonstrated that RGP reduced glioma cell viability and attenuated glioma cell locomotion in GBM8401 and U87MG cells. RGP treated cells had significant increase in the percentage of apoptotic cells and rise in the percentage of caspase-3 activity. In addition, the results of study's cell cycle analysis also showed that RGP arrested glioma cells at G2/M phase and Cell failure pass the G2 checkpoint by RGP treatment in GBM8401 Cells. Based on the above results, it seems to imply that RGP activated DNA damage checkpoint system and cell cycle regulators and induce apoptosis in established GBM cells. In conclusion, RGP can inhibit proliferation, cell locomotion, cell cycle progression and induce apoptosis in GBM cells in vitro.